Speaking of faith : cross-cultural perspectives on women, religion, and social change - Eck, Diana L.; Jain, Devaki, 1933; Harvard University (New Delhi : Kali for Women, 1986)
Papers presented at an international conference, 1983, organized by the Harvard University.
Includes bibliographical references.
Keywords: Women and religion -- Congresses; Religion and sociology -- Congresses; Feminism -- Religious aspects -- Congresses; Social change -- Congresses